2013
DOI: 10.3109/0886022x.2013.835266
|View full text |Cite
|
Sign up to set email alerts
|

Non-albuminuric renal disease among subjects with advanced stages of chronic kidney failure related to type 2 diabetes mellitus

Abstract: Urinary albumin excretion has been consistently found to be normal in a significant number of subjects with early stages of diabetic kidney disease. This study was aimed to estimate the prevalence and characteristics of non-albuminuric chronic kidney disease associated with type 2 diabetes mellitus among subjects who reach advanced stages of renal failure. Study population was composed of incident patients with advanced chronic kidney disease (glomerular filtration rate 530 mL/min) related to type 2 diabetes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 23 publications
2
32
0
4
Order By: Relevance
“…In the present study, only 2 subjects were excluded as they showed missing values for blood hemoglobin levels; subsequently, the final sample size consisted of 382 participants. Detailed information of this survey has been described elsewhere [21,22] .…”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…In the present study, only 2 subjects were excluded as they showed missing values for blood hemoglobin levels; subsequently, the final sample size consisted of 382 participants. Detailed information of this survey has been described elsewhere [21,22] .…”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…Mesangial matrix proliferation, increased glomerular fibrosis, thickening of basement membrane, and increased type IV collagen in the interstitium and glomeruli are some pathological changes that were demonstrated in NADKD rats and patients [12]. Moreover, a faster eGFR decline in albuminuric DM patients was observed as compared with patients with NADKD [13]. Urinary NGAL and FABP are the important indicators of tubular injury in the kidney [14] that may be helpful in the diagnosis of NADKD.…”
mentioning
confidence: 99%
“…En cambio, la etiología de la ERD-NA en diabéticos tipo 2 podría ser más variable. Desafortunadamente, aunque la ERD-NA en diabéticos tipo 2 ha sido descrita en una gran variedad de estudios, en ellos se hace diferenciación respecto a características clínicas y hábitos entre su condición normoalbuminúrica vs. microalbuminuria o macroalbuminuria, sin recurrir a la biopsia renal para obtener un diagnostico definitivo [2][3][4][5][6][7] .…”
Section: Discussionunclassified
“…La prevalencia de esta enfermedad [2][3][4] varía entre 25 % a 50 % de los pacientes que exhiben TFG menor a 60 ml/min/1,73mt2. Los pacientes con ERD-NA presentan características diferentes a la población albuminúrica, tales como: mayor proporción de sexo femenino, edad mayor, menor TFG, buen control de la presión arterial, raza blanca no hispanos, menor prevalencia de tabaquismo y mayor prevalencia de polineuropatía [5][6][7] .…”
Section: Introductionunclassified